DEVELOPMENT OF PHYSICAL FITNESS OF BASKETBALL PLAYERS IN THE INITIAL TRAINING GROUP (Zamonaviy ilmiy-texnik tadqiqotlar, 2026)
This article explores the crucial aspects of physical fitness development in basketball players within the initial training group. Physical fitness plays a pivotal role in enhancing performance, preventing injuries, and promoting long-term athlete development. The study delves into the specific training methodologies, drills, and strategies employed to improve the physical fitness of novice basketball players. By assessing the development of key fitness components such as cardiovascular endurance, strength, agility, and coordination, this research provides valuable insights into optimizing training programs for early-stage basketball athletes. The findings highlight the importance of tailored training regimens and the potential benefits for the overall skill acquisition of basketball players.